The Influence of Brand Ambassadors and Brand Credibility on Purchase Decisions of Glad2Glow Skincare Products on TikTok in Bandung City - Della Kurnia Febrianti; Muji Rahayu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of brand ambassadors and brand credibility on purchase decisions among consumers of Glad2Glow skincare products through the TikTok platform in Bandung. A sample of 100 respondents was determined using the Lemeshow formula with purposive sampling technique. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 21. The results show that both partially and simultaneously, brand ambassadors and brand credibility have a positive and significant effect on purchase decisions, highlighting the importance of utilizing credible brand ambassadors and strengthening brand credibility to enhance purchase decisions in social commerce contexts.